Current state and development of agricultural products exports of the Republic of Uzbekistan - Janabay, Isakov; Gulbahar, Tajenova; Gulayda, Turdiyeva; Alisher , Qurbanov; Ilkhambek, Isakov (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, in Uzbekistan, there was carried out major reforms in all areas, and there have been major changes in the field of agriculture. This article is about the role of agriculture in the economy and development of the country. The indicators of export of agricultural products of the Republic of Uzbekistan are analyzed. The experience of the USA, Canada and several European countries, as well as the experience of the main countries exporting agricultural products, shows that all of them are developing new markets for their products and national producers will ensure production growth based on export support programs. The program’s activities are aimed at improving the competitiveness of domestic agricultural products in foreign markets, developing new markets for domestic agricultural raw materials and processed products, as well as ensuring the availability of financial instruments for national exporters.